An Exploratory Analysis of Cost of Covid-19 Vaccines in India - Pal Singh, Netra; Sorout, Aradhana (Industrija, 2023)
This research paper presents a status analysis of cost of Covid-19 vaccines in India. The status analysis includes cost of different vaccines and changes made by the Central Government in the fixing or changing prices of vaccines during pandemic. Efforts of Central Government in ramping up vaccine production, and procurement. In addition, research paper elaborates the challenges faced with respect to communication and making large population aware about benefits of vaccination, commitment and responsibility of Government of India about the vaccination program to save life of its citizens. Based on the research, it is concluded that India is the only country which is not forcing its citizens to pay for vaccines and vaccinated large part of the population, and caped the prices to an optimal level as compared to other economies. It is also observed that awareness about vaccines availability, efficacy, and price among urban and semi-urban people of all age and gender is very high but still the vaccination penetration was low initially due to economic and social factors. Based on the analysis it is suggested that health sector should be made part of concurrent list of Union of India so that central government and state government can fight future scenarios together more effectively.